Faba Bean Breeding in Australia: Past, Present and Future - Kedar N. Adhikari; Samuel C. Catt; Frederick L. Stoddard (Legume Science, 2025)
ABSTRACT Faba bean is an important autumn‐sown grain legume in Australia, coming third in production and hectarage after lentil and chickpea. It is mostly grown in South Australia, Victoria, New South Wales (NSW) and Queensland (QLD). Despite its introduction as early as European settlement in Australia, the crop did not get much attention until the 1970s, when research on it as a crop was initiated at the Waite Institute of the University of Adelaide and cultivar ‘Fiord’ was released for general cultivation in 1980. Production gradually increased and spread to other states, mainly Victoria and NSW. Two coordinated breeding nodes addressing distinct agroecological zones and disease spectra were subsequently established. The breeding node at the University of Adelaide is responsible for breeding long‐season and Ascochyta‐resistant cultivars for the Mediterranean‐climate southern region, while the node at the University of Sydney is responsible for breeding short‐season and rust‐resistant cultivars for the subtropical area of northern NSW and southern QLD. Initially, the northern node was with the NSW Department of Primary Industries. Improved cultivars have been released from both organisations for their respective areas, leading to increased productivity. Rust in the north and Ascochyta in the south are the main diseases, while chocolate spot is a concern in both areas. In addition to increasing yield and disease resistance, both programmes also aim to improve herbicide resistance and seed quality, with reduced vicine–convicine content as an early target. Limited work has been done towards molecular breeding until now, but with the availability of a full genome sequence, resources can be directed towards genomic selection for faster genetic gain.